A man's blessing or a woman's curse? The Family-earnings gap of doctors - Kühnle, Daniel; Schurer, Stefanie; Cheng, Terence; Scott, Anthony (Industrial relations, 2016)

Bounding the causal effect of unemployment on mental health - nonparametric evidence from four countries - Cygan-Rehm, Kamila; Kühnle, Daniel; Oberfichtner, Michael (Health Economics, 2017)

Früher in den Kindergarten, besser gerüstet ins Leben? - Kühnle, Daniel; Oberfichtner, Michael (IAB-Forum, 2018)
Dass ein früher Kindergartenbesuch die Entwicklungschancen von Kindern - und damit zugleich deren spätere Leistungen in Schule und Beruf - verbessert, ist eine auch von Experten immer wieder vertretene These. Eine aktuelle Studie der Universität Erlangen-Nürnberg und des IAB findet dafür allerdings keine Anhaltspunkte - möglicherweise mit einer Ausnahm
Keywords: Chancengleichheit

How effective are pictorial warnings on tobacco products? New evidence on smoking behaviour using Australian panel data - Kühnle, Daniel (Journal of Health Economics, 2019)
Studies examining the introduction of pictorial warnings on cigarette packages provide inconclusive evidence due to small samples and methodological issues. We use individual-level panel data from Australia to examine the association between pictorial warnings and smoking behaviour – prevalence, quitting, initiating and relapsing. The pictorial warnings were accompanied by a reference to a smoking cessation helpline and supportive television commercials. Applying an event study framework, we show that the reform reduced smoking rates by around 4% within the first year of the policy. The effect decreases with age, is similar for men and women, and is slightly larger for low-educated compared to high-educated individuals. The reform permanently lowered smoking rates primarily due to increased quitting in the year of the reform. Thus, pictorial warnings combined with a reference to a smoking cessation helpline and supportive media campaigns are an important tobacco control measure to reduce the social costs of smoking.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Cessation; Pictorial warnings; Smoking; Smoking initiation; Smoking relapse

Längere Elternzeiten haben langfristig keine negativen Auswirkungen auf die Betriebe - Huebener, Mathias; Jessen, Jonas; Kühnle, Daniel; Oberfichtner, Michael (2024)
Die Einführung des Elterngeldes im Jahr 2007 führte bei vielen Müttern zu längeren Auszeiten. In den betroffenen Betrieben entstanden dadurch größere Beschäftigungslücken, die sie nur teilweise ausgeglichen haben. Auf längere Sicht sind jedoch keine nachteiligen Folgen auf die Beschäftigung, die Lohnsumme oder gar den Fortbestand der betroffenen Betriebe festzustelle
Keywords: Betriebe; Elterngeld; Elternzeit; Frauen; Vereinbarkeit von Beruf und Familie

Paid parental leave and child health in Australia - Kühnle, Daniel; Broadway, Barbara; Kalb, Guyonne; Maeder, Miriam (Economic Record, 2017)
Keywords: Gender

Paid parental leave and families' living arrangements - Riphahn, Regina Therese; Cygan-Rehm, Kamila; Kühnle, Daniel (Labour Economics, 2018)
Keywords: Gender

Parental leave policies and socio-economic gaps in child development: Evidence from a substantial benefit reform using administrative data - Huebener, Mathias; Kühnle, Daniel; Spiess, C. Katharina (Labour Economics, 2019)
This paper examines the effects of substantial changes in paid parental leave on child development and socio-economic development gaps. We analyse a German reform that replaced a means-tested with an earnings-related benefit scheme. Higher-income households benefited relatively more from the reform than low-income households. The reform expanded paid leave in the first year, while it removed paid leave in the second year after childbirth. We compare children born around the eligibility cut-off on January 1st 2007 and contrast them with children from the preceding, unaffected cohort within a difference-in-differences approach. The analysis is based on administrative data from mandatory school entrance examinations containing detailed child development assessments at age six. Our precise and robust estimates reveal no effects of the changes in parental leave benefits on child development across various socio-economic groups, and consequently no effects on socio-economic development gaps. However, based on administrative employment data, we document substantial effects on maternal employment and family income. The paper concludes that reform effects on today's mothers are not sacrificed by increases in SES gaps of the future workforce.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Child development; Elterngeld; Language skills; Motor skills; Parental leave benefits; School readiness; Socio-emotional stability; Gender

The Causal Effect of Family Income on Child Health in the UK - Kühnle, Daniel (Journal of Health Economics, 2014)

The effects of smoking bans on self-assessed health: Evidence from Germany - Kühnle, Daniel; Wunder, Christoph (Health Economics, 2017)

Using the life satisfaction approach to value daylight savings time transitions. Evidence from Britain and Germany - Kühnle, Daniel; Wunder, Christoph (Journal of Happiness Studies, 2016)

What factors affect doctors’ work decisions: Comparing structural discrete choice and reduced-form approaches - Kühnle, Daniel; Kalb, Guyonne; Scott, Anthony; Cheng, Terence; Jeon, Sunghee (Health Economics, 2017)